100m and 110m hurdles drills - Knight, G. (The Best of British Track & Field Drills Series, 2009)
With over 40 years of coaching experience, Graham Knight is undoubtedly one of the world's leading authorities on hurdles. In this DVD, Knight shares his wealth of expertise with you presenting the drills that develop the technical elements of the 100 & 110M hurdles. Knight begins with the lead leg technique that includes technical breakdown and drill progressions in a walk, skip, run sequence. Knight's lead leg philosophy is "time in the air is time wasted," and his hurdle drills focus upon getting the lead leg down quickly. Next, Knight switches his technical breakdown to the trail leg and includes hurdling techniques and drills to keep the body "tall" as well as techniques for teaching proper arm mechanics. Knight includes on-ground mobility exercises and trail leg isolation drills. Knight combines the lead and trail leg skills into the complete hurdle technique. Let Graham Knight show you how to incorporate speed without compromising technique. This videos are a great way to learn drills and skills for the beginning and intermediate coach and athlete. This video has two international level hurdlers wording side by side with the coach demonstrating the drills, some basic and others more difficult.